Validity of a Measure of Dual-task Performance Using the Dynamic Gait Index for Patients with Stroke - KAGAWA, Kojiro; HARADA, Kazuhiro; HIRAGAMI, Shogo; INOUE, Yu; SATO, Yukari (Rigakuryoho Kagaku, 2012)
[Purpose] To determine the criterion-related validity of a measure of dual-task performance using the dynamic gait index (DGI) for patients with stroke. [Subjects] Seventeen patients with stroke who were capable of walking unassisted and had no cognitive impairments. [Methods] We evaluated the DGI, stops walking when talking test (SWWT), timed up and go test, walking speed, and step length under the dual-task condition. To determine the criterion-related validity, we first, performed correlation analysis of the DGI scores and the results of each evaluation. Next, we classified subjects into two groups, continued walking group or stops walking group using the results of SWWT, and then, we compared the DGI scores between the two groups. [Results] DGI scores showed significantly strong correlations with each result under the dual-task condition. The average DGI score of the continued walking group was significantly higher than that of the stops walking group. [Conclusion] The DGI showed evidence of criterion-related validity. It is a useful measure for evaluating the dual-task performance of patients with stroke.